Incidence and Risk Factors for the Development of Acute Colonic Pseudo-Obstruction (Ogilvie Syndrome) in Total Joint Arthroplasty Patients. Issue 4 (15th February 2021) - Hsiue, Peter P.; Greig, Danielle; Chen, Clark J.; Patel, Bobby; Trikha, Rishi; Rowan, Fiachra E.; Khoshbin, Amir; Stavrakis, Alexandra I.
Abstract : Background: Acute colonic pseudo-obstruction (Ogilvie syndrome [OS]) is a rare but devastating condition that can develop in orthopaedic patients postoperatively. The objective of this study was to identify the risk factors for developing OS after total hip arthroplasty (THA) or total knee arthroplasty (TKA) and to compare the outcomes between patients who did and did not develop OS postoperatively. Methods: This was a retrospective review using the National Inpatient Sample, a national database incorporating inpatient hospitalization information. ICD-9 codes were used to identify patients who underwent primary and revision THA or TKA. Patients were separated based on the diagnosis of OS. Primary outcomes assessed included patient mortality, postoperative complications, length of stay, and cost during index hospitalization. Results: From 2001 to 2014, a total of 12, 541, 169 patients underwent primary and revision THA or TKA. Of those, 3, 182 patients (0.03%) developed OS postoperatively. There was an increased incidence of OS in revision THA and TKA compared with primary THA and TKA. Fluid and electrolyte disorders were associated with the largest increased adjusted risk of OS. Patients with OS had an increased adjusted risk of overall postoperative complications and being discharged to skilled nursing facility. Patients with OS had an increased average length of stay and hospitalization cost compared with patients without OS. Discussion: Given our findings, the risk factors for the development of OS, including revision surgery, should be identified and minimized during the perioperative period to prevent the development of this morbid and potentially life-threatening complication. Level of Evidence: III (Retrospective cohort study).